Politeness Strategy on Social Interaction Used by Munanese - ' Yetty (Hasanuddin University, 2018)
This study aims to investigate the differences of politeness strategy used by Munanese in their social interaction. The source of the data was verbal utterances of Munanese dialect Gu . This study used pragmatic study especially theory of politeness by Brown and Levinson, and supported by other theory particularly Yassi’s theory. It also used descriptive qualitative method that is observation by recording and note taking. The result of the study showed the pattern politeness strategies used in Munanese Dialect Gu are; Hormat Non Kerabat; mixed, Hormat berkerabat; mixed and positive politeness (KP), Akrab Non Kerabat; mixed, Akrab Berkerabat; positive politeness (KP), Hierarki Non Kerabat; mixed (hierarchy), and (6) Hierarki Kerabat; mixed. The differences of the strategies maybe caused by several possible reasons including cultural differences, different age and social status when the people interact each other.Keyword : politeness, social interaction, pragmatic